Are perceptions of self‐efficacy in preventing falls by persons with Alzheimer's disease or related dementias considered by their family caregivers?: Developing topics. (7th December 2020) - Panzer, Victoria; Smith, Veronica; Wakefield, Dorothy; Fortinsky, Richard H; Maher, Joanne
Abstract: Background: Falls are common in Persons with Alzheimer's disease and related dementias (PwADRD) which may be affected by their self‐efficacy or that of their Family Caregivers (CGs). Our earlier studies demonstrated that older adults may be over‐confident or timid and we explored whether CG's self‐efficacy in preventing a fall or loss of balance (FLOB) for their PwADRD considered PwADRD confidence. Method: Activity‐Specific Balance Confidence (ABC) is a standardized scale in which confidence in preventing a FLOB is rated (0=no confidence to 10=completely confident) in 16 specific situations. Pilot testing with standard 0‐10, 5 or 3 point Likert scales was unsuccessful with PwADRD. Therefore, CGs self‐administered the ABC, rating their confidence (0‐10) in preventing PwADRD FLOBs, while the PwADRD responded 'Yes I Can' or 'No I Can't' prevent a FLOB to trained Interviewers for each situation. ABCtotal (CG 0‐160, PwADRD 0‐16) and Spearman correlation between CG and PwADRD ABCtotal scores were calculated. Wilcoxon two sample tests compared CG ratings between groups (PwADRD who responded Yes and those who responded No) for each situation. Result: Thirty‐three dyads were 85% White, 3‐6% Asian, African‐American, Hispanic or Pacific‐Islander. CGs were 91% female, average age=70.3 and ABCtotalmean=105.2, SD(26.3). PwADRD were 76% male, average age=77.2, MMSE score mean=22.3, SD(6.4) and ABCtotalmean=12, SD(2.6). The correlation between CG and PwADRD ABCtotal scores (r=0.349) was significant (p=.046). We compared CG ratings between the two groups (PwADRD who responded Yes or No) for each situation. Overall, PwADRD were confident they could prevent a FLOB. In six situations, there were 3 or less who responded No, I can't. The CG median rating for the Yes group was significantly higher than the No group in only three situations: walk in crowd (8 vs. 5, p=.008), icy sidewalks (6 vs. 2, p=.047), and bend over (8 vs. 5.5, p=.058). In all other situations, there was no significant difference in CG ratings whether the PwADRD responded Yes or No. Conclusion: In many situations, CG's self‐efficacy for preventing FLOBs was similar irrespective of PwADRD confidence. This 'Dual‐ABC' approach may help to focus falls prevention interventions on situations in which the CG's self‐efficacy does not consider the PwADRD's confidence.